1995
DOI: 10.1177/08959374950090010101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fluoride-Supplemented Sucrose on Experimental Dental Caries and Dental Plaque PH

Abstract: Sucrose, 5% and 10% (w/v), supplemented with between 0 and 5 ppm fluoride (F), was tested for its influence in vitro on plaque-induced experimental in vitro enamel caries and plaque pH. Plaque growth on bovine enamel was initiated from saliva inocula and sustained in a multiple plaque growth system for up to 31 days by means of a basal medium with periodic applications of sucrose or sucrose supplemented with F. Change in enamel mineralization was assessed, before and after plaque growth, by microhardness testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…It is these latter e¡ects that seem to be most pertinent to the antimicrobial^anticaries properties of £uoride. Fluoride can even have an anticaries e¡ect when added to sucrose in the diet [28,84] and can act in concert with other anticaries agents [40,41,121]. Moreover, £uoride appears to have important ecological e¡ects on dental plaque in that it acts to reduce acidi¢cation and in the long run serves to select for a less acid-tolerant, less cariogenic microbiota, as suggested by, for example, Marsh [75].…”
Section: Weak Acids and Dental Cariesmentioning
confidence: 99%
“…It is these latter e¡ects that seem to be most pertinent to the antimicrobial^anticaries properties of £uoride. Fluoride can even have an anticaries e¡ect when added to sucrose in the diet [28,84] and can act in concert with other anticaries agents [40,41,121]. Moreover, £uoride appears to have important ecological e¡ects on dental plaque in that it acts to reduce acidi¢cation and in the long run serves to select for a less acid-tolerant, less cariogenic microbiota, as suggested by, for example, Marsh [75].…”
Section: Weak Acids and Dental Cariesmentioning
confidence: 99%
“…It is these latter effects that seem to be most pertinent to the antimicrobial–anticaries properties of fluoride. Fluoride can even have an anticaries effect when added to sucrose in the diet [28,84] and can act in concert with other anticaries agents [40,41,121]. Moreover, fluoride appears to have important ecological effects on dental plaque in that it acts to reduce acidification and in the long run serves to select for a less acid‐tolerant, less cariogenic microbiota, as suggested by, for example, Marsh [75].…”
Section: Weak Acids and Dental Cariesmentioning
confidence: 99%
“…The above explanation could partly be validated if no deposition of fluoride in plaque had occurred. This was not tested in the study but has been demonstrated in a similar experimental design by Cutress et al (1995). The fact that the blocks were exposed to sugar and fluoride extraorally means that the plaque-enamel complex was not exposed to the salivary flow which would have been stimulated by the sucrose content.…”
Section: Discussionmentioning
confidence: 84%